Using CRISPR-Cas9 Technology to Eliminate Xyloglucan in Tobacco Cell Walls and Change the Uptake and Translocation of Inorganic Arsenic - Wang, Meng; Song, Xinxin; Guo, Shuaiqiang; Li, Peiyao; Xu, Zongchang; Xu, Hua; Ding, Anming; Ahmed, Rana Imtiaz; Zhou, Gongke; O’Neill, Malcom; Yang, Dahai; Kong, Yingzhen (Frontiers in Plant Science, 2022)
Xyloglucan is a quantitatively major polysaccharide in the primary cell walls of flowering plants and has been reported to affect plants’ ability to tolerate toxic elements. However, it is not known if altering the amounts of xyloglucan in the wall influences the uptake and translocation of inorganic arsenic (As). Here, we identified two Nicotiana tabacum genes that encode xyloglucan-specific xylosyltransferases (XXT), which we named NtXXT1 and NtXXT2. We used CRISPR-Cas9 technology to generate ntxxt1, ntxxt2, and ntxxt1/2 mutant tobacco plants to determine if preventing xyloglucan synthesis affects plant growth and their ability to accumulate As. We show that NtXXT1 and NtXXT2 are required for xyloglucan biosynthesis because no discernible amounts of xyloglucan were present in the cell walls of the ntxxt1/2 double mutant. The tobacco double mutant (ntxxt1/2) and the corresponding Arabidopsis mutant (atxxt1/2) do not have severe growth defects but do have a short root hair phenotype and a slow growth rate. This phenotype is rescued by overexpressing NtXXT1 or NtXXT2 in atxxt1/2. Growing ntxxt mutants in the presence of AsIII or AsV showed that the absence of cell wall xyloglucan affects the accumulation and translocation of As. Most notably, root retention of As increased substantially and the amounts of As translocated to the shoots decreased in ntxxt1/2. Our results suggest that xyloglucan-deficient plants provide a strategy for the phytoremediation of As contaminated soils.